Feedback survey on usability of enbora method for assessing an exposure to risk factors related to wmsds - A Rahman, M N; A Rahman, S A (IOP Publishing, 2019)
Entire Body Risk Assessment (ENBORA) method is a new observational method assessing the risk factors that contributed with Work-related Musculoskeletal Disorders (WMSDs). To evaluate the effectiveness and ease of use of a new observational method, the usability testing is needed. This research aimed to study the usability analysis of the ENBORA method. 16 participants were involved in a day ENBORA training session. All sixteen participants were required to assess the usability of ENBORA method using feedback questionnaire. Majority of the participants agreed that it was easy to understand and use the ENBORA at work. In order to provide a simple and comprehensible interface of ENBORA, usability test had to be performed. After conducting the usability testing, some improvements were made to the ENBORA method after taking the respondents’ comments and suggestions into account.